Mapping of Indonesia’s Agricultural Insecticides in 2021: Registered Products, Future Research Opportunities, and Information Dissemination - Ignatius Putra Andika; Edhi Martono (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Since the onset of green revolution in Indonesia, insecticides have become an indispensable tool to manage insect pests. However, the increasing concern over human and environmental health, coupled with the establishment of insecticide-resistance insect populations, has urged the reduction of chemical insecticide use. But as safer novel technologies suffer in their availability, result reliability, practicality, and cost-results efficiency that farmers seek; chemical insecticides remain the option for many farmers. Understanding insecticides availability to Indonesian farmers and their current uses and situation. The pin point was made to maximize their effectiveness and later reduce risk caused by their use. Pyrethroid was the most registered insecticide group followed by other broad-spectrum insecticide groups, such as organophosphates and carbamates. Insect insecticide resistances have been evaluated for many major insect pests in high-value commodities and staple crops, unfortunately it misses several important species. This review used initial data to demonstrate knowledge gaps that still require further research and suggested research themes which may counter these opportunities. Besides, it suggests a working framework to enhance technology adoption by farmers. Reducing chemical insecticide should be a common goal and a collaborative effort, and in order to divert the adverse effects while maximizing their effectivity in the field.